A new multi-processor architecture for parallel lazy cyclic reference counting - Lins, R. D. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2005: Anais do XVII International Symposium on Computer Architecture and High Performance Computing, 2005)
Reference counting is the memory management technique of most widespread use today. This paper presents a new multi-processor architecture for parallel cyclic reference counting. In this architecture, there is no direct mutator-collector communication and synchronization is kept minimal.